2019
DOI: 10.1073/pnas.1903856116
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Officer characteristics and racial disparities in fatal officer-involved shootings

Abstract: Despite extensive attention to racial disparities in police shootings, two problems have hindered progress on this issue. First, databases of fatal officer-involved shootings (FOIS) lack details about officers, making it difficult to test whether racial disparities vary by officer characteristics. Second, there are conflicting views on which benchmark should be used to determine racial disparities when the outcome is the rate at which members from racial groups are fatally shot. We address these issues by crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 26 publications
0
65
2
Order By: Relevance
“…This is the foundational fact on which our paper was based. What is clear from the above examples (and also more systematic and full analyses by e.g., Nix, Campbell, Byers, and Alpert (2017) and Johnson, Tress, Burkel, Taylor, and Cesario (2019)), is that violent crime is the context of fatal police shootings. Yes, shootings of unarmed and nonviolent citizens do occur, but they are a small minority of cases.…”
Section: Violent Crime As a Benchmarkmentioning
confidence: 96%
“…This is the foundational fact on which our paper was based. What is clear from the above examples (and also more systematic and full analyses by e.g., Nix, Campbell, Byers, and Alpert (2017) and Johnson, Tress, Burkel, Taylor, and Cesario (2019)), is that violent crime is the context of fatal police shootings. Yes, shootings of unarmed and nonviolent citizens do occur, but they are a small minority of cases.…”
Section: Violent Crime As a Benchmarkmentioning
confidence: 96%
“…The first critique of Johnson et al (2019) centers around the idea that the only quantity of interest in understanding racial bias in fatal police shootings is Pr(shot|race, X), that is, the probability of being shot given a civilian's race and some covariates. Thus, according to Knox and Mummolo (2019), Pr(race|shot, X) does not provide any useful information in understanding the topic of race and police shootings.…”
Section: Critique 1: Informational Value Of Pr(race|shot X)mentioning
confidence: 99%
“…Research on realworld policing behavior indicates fatal shootings are strongly tied to situations where violent crime is committed (Klinger, Rosenfeld, Isom, & Deckard, 2016). This is reflected in the fact that between 85% -90% of fatal police shootings involve armed civilians (Johnson et al, 2019;Nix, Campbell, Byers, & Alpert, 2017). While we do not know the exact rate at which police encounter Black and White individuals in the context of violent crime, we can estimate these rates from several different proxies.…”
Section: Transformation Of Pr(race|shot) To Pr(shot|race)mentioning
confidence: 99%
See 1 more Smart Citation
“…While we believe the problem we cover here is the most critical issue with this paper, there are other methodological issues present in this paper including, among others, issues with the reliability of The Counted data (which can use media reports based only on police reports), base rate neglect (for a broader discussion of issues with administrative data on police shootings seeKnox et al 2019), and contradictory results found in other papers which are not adequately explained(Ross 2015). In particular, we would like to note the extensive criticism by Ulrich Schimmack and Rickert Carlsson of a similar publication by many of these same authors(Johnson et al 2019), which notes a number of serious flaws in that publication as well (Schimmack 2019).…”
mentioning
confidence: 90%